Childhood maltreatment predicts poorer executive functioning in adulthood beyond symptoms of internalizing psychopathology. (August 2021) - Letkiewicz, Allison M.; Funkhouser, Carter J.; Shankman, Stewart A.
Abstract: Background: A history of childhood maltreatment predicts poorer functioning in several domains during childhood, including executive function (EF). While there is also evidence of poorer EF in adults with a history of childhood trauma, results are mixed. Notable limitations of previous research are (a) the use of single indicators of EF, and/or (b) not consistently assessing whether childhood maltreatment predicts poorer EF beyond internalizing psychopathology. Objective: We sought to overcome limitations of prior work by examining relationships between childhood maltreatment and EF in adulthood by using a latent factor of EF derived from multiple indicators and including psychopathology covariates in our analyses. Participants and setting: The present study included a large sample of community adults ( n  = 489) who were oversampled for internalizing psychopathology symptoms. Methods: Primary analyses examined whether childhood maltreatment (cumulative and subtypes) predicted EF using a latent factor approach and linear mixed effects models. Follow-up analyses assessed the impact of childhood maltreatment on EF beyond internalizing psychopathology symptoms and assessed whether gender moderated relationships between EF and childhood maltreatment. Results: Greater cumulative maltreatment predicted poorer EF ( B  = -0.15), and emotional neglect emerged as a unique predictor of EF ( B  = -0.18). These results remained after controlling for psychopathology symptoms. Gender moderated the relationship between physical abuse and EF, with physical abuse predicting poorer EF among males ( B  = 0.30), but not females ( B  = -0.04). Conclusions: Overall, results indicate that general EF deficits are related to a history of childhood maltreatment, which is not accounted for by internalizing psychopathology symptoms. Potential implications and future directions are discussed.